Bilateral spontaneous carotid⁃cavernous fistula: a case report - Jing⁃jing CHE; Xu CHEN; Yan⁃jun GUO; Hou⁃zhen TUO; Jia⁃wei WANG; Ji⁃mei LI (Chinese Journal of Contemporary Neurology and Neurosurgery, 2012)
DOI：10.3969/j.issn.1672⁃6731.2012.02.026